Transformational Leadership in Youth Empowerment to Foster Social Creativity and Innovation - Arfanaldy, Sehan Rifky; Kamil, Mustofa; Hardian, Dafyar Eliadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
This article explores the role of transformational leadership in youth empowerment to promote creativity and social innovation as part of a sustainable human resource development effort. Youth are vital national assets with great potential to contribute to social, economic, and cultural advancement. However, the lack of visionary leadership support often hinders the optimization of their potential. This study employs a qualitative descriptive approach using a literature review method to examine relevant theories and previous research related to leadership, empowerment, and innovation. The findings reveal that transformational leadership enhances youth participation, creativity, and social responsibility through inspirational, communicative, and collaborative approaches. Transformational leaders act not only as policymakers but also as facilitators who foster a spirit of change and independence. Youth empowerment based on creativity and innovation has proven effective in strengthening competitiveness and driving positive social transformation. Therefore, the application of transformational leadership principles is an essential strategy in shaping young generations who are characterized, adaptive to change, and actively contribute to sustainable development.